Video recording emergency care and video-reflection to improve patient care; a narrative review and case-study of a neonatal intensive care unit - Heesters, Veerle; Witlox, Ruben; van Zanten, Henriette A.; Jansen, Sophie J.; Visser, Remco; Heijstek, Veerle; Te Pas, Arjan B. (Frontiers in Pediatrics, 2022)
As the complexity of emergency care increases, current research methods to improve care are often unable to capture all aspects of everyday clinical practice. Video recordings can visualize clinical care in an objective way. They can be used as a tool to assess care and to reflect on care with the caregivers themselves. Although the use of video recordings to reflect on medical interventions (video-reflection) has increased over the years, it is still not used on a regular basis. However, video-reflection proved to be of educational value and can improve teams’ management and performance. It has a positive effect on guideline adherence, documentation, clinical care and teamwork. Recordings can also be used for video-reflexivity. Here, caregivers review recordings together to reflect on their everyday practice from new perspectives with regard to context and conduct in general. Although video-reflection in emergency care has proven to be valuable, certain preconditions have to be met and obstacles need to be overcome. These include gaining trust of the caregivers, having a proper consent-procedure, maintaining confidentiality and adequate use of technical equipment. To implement the lessons learned from video-reflection in a sustainable way and to continuously improve care, it should be integrated in regular simulation training or education. This narrative review will describe the development of video recording in emergency care and how video-reflection can improve patient care and safety in new ways. On our own department, the NICU at the LUMC, video-reflection has already been implemented and we want to further expand this. We will describe the use of video-reflection in our own unit. Based on the results of this narrative review we will propose options for future research to increase the value of video-reflection.